PERPANJANGAN HAK GUNA BANGUNAN YANG MASIH TERKAIT HAK TANGGUNGAN ( STUDI KASUS PT. BANK PEMBANGUNAN DAERAH SUMATERA BARAT CABANG KOTA PEKAN BARU) - , Yulita Anggraini Indah, Prof. DR. Nurhasan Ismail, SH., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to To know and understand the process of extension of Right of that is still bound in the Bank's mortgage and to know, understand and analyze the result of legal right to build over his right but still be in the bank guarantee. This study is descriptive, ie to obtain an objective overview of a particular situation in terms of certificate of right to build an extension that is still tied mortgage and the method used is the juridical sociological research is done on the problem by looking in terms of legislation in force and is connected with the facts found in the field. This study is a data search activities of primary and secondary data using primary legal materials, legal materials secondary and tertiary legal materials. Analysis of the data used in this study is to use qualitative methods in a way inventory, arrange them systematically, and then interpret them, relate to one another, linked to the problems studied by looking at the rules of laws, after it was formulated in the form of a description and finally withdrawn conclusions in response to the issues addressed to the Field Research Officer PT. Regional Development Bank of West Sumatra city of Pekanbaru Branch, Office of Land Agency officials Pekanbaru and Notary / PPAT. From this research it is known that prior Right to Build period ended right has been extended, then the dependents do not have time right to delete, so it remains a burden Right to Build an extended, while the renewal of Right to Build, delete the original rights and followed by later given to the The same owners with new rights. cause the non-fulfillment of the principles that must be met in specialitas Mortgage loading and effect of law if the Right to Build object Mortgage Mortgage ending resulted in abolition.